Clustered Genes Encoding 2-Keto-l-Gulonate Reductase and l-Idonate 5-Dehydrogenase in the Novel Fungal d-Glucuronic Acid Pathway - Kuivanen, Joosu; Arvas, Mikko; Richard, Peter (Frontiers in Microbiology, 2017)
D-Glucuronic acid is a biomass component that occurs in plant cell wall polysaccharides and is catabolized by saprotrophic microorganisms including fungi. A pathway for D-glucuronic acid catabolism in fungal microorganisms is only partly known. In the filamentous fungus Aspergillus niger, the enzymes that are known to be part of the pathway are the NADPH requiring D-glucuronic acid reductase forming L-gulonate and the NADH requiring 2-keto-L-gulonate reductase that forms L-idonate. With the aid of RNA sequencing we identified two more enzymes of the pathway. The first is a NADPH requiring 2-keto-L-gulonate reductase that forms L-idonate, GluD. The second is a NAD+ requiring L-idonate 5-dehydrogenase forming 5-keto-gluconate, GluE. The genes coding for these two enzymes are clustered and share the same bidirectional promoter. The GluD is an enzyme with a strict requirement for NADP+/NADPH as cofactors. The kcat for 2-keto-L-gulonate and L-idonate is 21.4 and 1.1 s-1, and the Km 25.3 and 12.6 mM, respectively, when using the purified protein. In contrast, the GluE has a strict requirement for NAD+/NADH. The kcat for L-idonate and 5-keto-D-gluconate is 5.5 and 7.2 s-1, and the Km 30.9 and 8.4 mM, respectively. These values also refer to the purified protein. The gluD deletion resulted in accumulation of 2-keto-L-gulonate in the liquid cultivation while the gluE deletion resulted in reduced growth and cessation of the D-glucuronic acid catabolism.